Ujaran Kebencian Warganet pada Kolom Komentar Akun Instagram @ahmadsahroni88 - Syehilla Syehilla; Markhamah Markhamah (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2026)
This study aims to describe various forms of hate speech and analyze the factors underlying the emergence of hate speech in the comments column of the Instagram account @ahmadsahroni88. The study was conducted using a qualitative and descriptive approach, because it focuses on understanding social phenomena through text analysis in the form of netizen comments containing hate speech. Data were obtained through documentation of comment screenshots and then analyzed using the Miles and Huberman interactive analysis model which includes the stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate that the forms of hate speech that emerged include the categories of insults, defamation, and provocation or incitement. These forms are manifested in curses, baseless accusations, prayers for evil, and calls to take negative actions against Ahmad Sahroni and his family. The factors underlying the emergence of hate speech include (1) internal factors withinnetizens; (2) low legal literacy and public ignorance regarding the boundaries between criticism and hate speech; (3) weak social control from both the environment and digital platforms; and (4) factors of public interest in the social and political context.